Mucoadhesive controlled-release formulations containing morin for the control of oral biofilms - de Farias, Aline Leite [UNESP] (2022)
This study aimed to evaluate the antimicrobial and anti-biofilm activity of morin on polymicrobial biofilms and its cytotoxicity in controlled-release films and tablets based on gellan gum. Polymicrobial biofilms were formed from saliva for 48 h under an intermittent exposure regime to 1% sucrose and in contact with films or tablets of gellan gum containing 2 mg of morin each. Acidogenicity, bacterial viability, dry weight and insoluble extracellular polysaccharides from biofilms were evaluated. The cytotoxicity of morin was evaluated in oral keratinocytes. Morin released from the systems reduced the viability of all the microbial groups evaluated, as well as the dry weight and insoluble polysaccharide concentration in the matrix and promoted the control of acidogenicity when compared with the control group without the substance. Morin was cytotoxic only at the highest concentration evaluated. In conclusion, morin is an effective agent and shows antimicrobial and anti-biofilm activity against polymicrobial biofilms.